Continuous arterial blood pressure indices and early hematoma expansion in patients with spontaneous intracerebral hemorrhage - Annerose Mengel; Vasileios Siokas; Rebecca Buesink; Sara Roesch; Kornelia Laichinger; Redina Ferizi; Efthimios Dardiotis; Patricia Schwarz; Jennifer Sartor-Pfeiffer; Constanze Single; Antje Giede-Jeppe; Till-Karsten Hauser; et al. (Brain Hemorrhages)
Objective: Blood pressure variability (BPV) and its potential association with early hematoma expansion (HE) in intracerebral hemorrhage (ICH) remains to be fully elucidated. Our study explores the potential link between BPV within the first 24 h after admission and HE in ICH. Methods: In a prospective cohort single-center study, we analyzed consecutive patients with spontaneous ICH. Continuous BP data via an arterial line extracted from the Intellispace Critical Care and Anesthesia information system (Philips Healthcare) were analyzed over 0–2, 0–8, 0–12, and 0–24 h intervals post-admission. BPV was assessed through successive variability (SV), standard deviation (SD), and coefficient of variation (CV) using all available BP measurements. Early HE was defined as an absolute [≥ 6 ml] or relative [≥ 33 %] increase in ICH volume on 24-hours follow-up brain imaging. Secondary endpoints were the influence of BP on admission and other potential risk factors for HE. Results: Among 305 ICH-patients (mean age ± SD 70.1 ± 14.9 years, 47.9 % female, median NIHSS 6 (3, 13), median ICH score 1 (1, 2)), 41 (13.4 %) experienced HE. HE-patients had higher NIHSS (p = 0.015), ICH-score (p = 0.005), ICH volume (p < 0.001) and higher pre-anticoagulation treatment (p = 0.004) on admission. There was no difference in BPV comparing ICH-patients with HE to those without. However, patients with HE had significantly lower diastolic BP (76.6 ± 14.8 vs. 86.3 ± 19.7 mmHg, p = 0.005) and MAP (103.2 ± 22.4 vs. 112.2 ± 22.6, p = 0.027) on admission. This pattern of lower diastolic BP persisted across the first 24 h. Logistic regression revealed larger ICH volume and pre-existing anticoagulation as significant predictors of HE, with higher initial diastolic BP reducing HE risk. Hemorrhages ≥ 30 cm3 showed significantly lower initial diastolic BP, MAP, and BPV across all time frames compared to ICH < 30 cm3. Conclusions: BPV within the first 24 h was not associated with HE. Lower diastolic BP on admission, anticoagulation use, and larger ICH volume are potential predictors for HE. However, larger hemorrhage size (>30 cm3) experienced lower absolute BP and BPV indices and worse clinical outcomes. These findings suggest a nuanced relationship between BP dynamics and ICH severity, underscoring the need for individualized BP management in acute ICH care. Further research is necessary to explore these relationships and optimize treatment strategies.